Pneumococcal Peritonitis: Still with Us and Likely to Increase in Importance - Darcy C Waisman; Gregory J Tyrrell; James D Kellner; Sipi Garg; Thomas J Marrie (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Pneumococcal peritonitis is uncommon and poorly understood.